A multichannel thiacalix[4]arene-based fluorescent chemosensor for Zn2+, F− ions and imaging of living cells. Issue 5 (2nd June 2016) - Ran, Mao-Qian; Yuan, Jian-Ying; Zhao, Yuan-Hui; Mou, Lan; Zeng, Xi; Redshaw, Carl; Zhao, Jiang Lin; Yamato, Takehiko
Abstract: The fluorescent sensor (3 ) based on the 1, 3-alternate conformation of the thiacalix[4]arene bearing the coumarin fluorophore, appended via an imino group, has been synthesised. Sensing properties were evaluated in terms of a colorimetric and fluorescence sensor for Zn 2+ and F − . High selectivity and excellent sensitivity were exhibited, and 'off-on' optical behaviour in different media was observed. All changes were visible to the naked eye, whilst the presence of the Zn 2+ and F − induces fluorescence enhancement and the formation of a 1:1 complex with3 . In addition, 3 exhibits low cytotoxicity and good cell permeability and can readily be employed for assessing the change of intracellular levels of Zn 2+ and F − . Abstract :